National assessment of health center readiness to train health profession students - Ianita Zlateva; Amanda Schiessl; May Oo; Meaghan Angers; Margaret Flinter (BMC Health Services Research)
Abstract Background In recent years, health centers in the United States have invested significant efforts to identify, develop, and implement various health professions training (HPT) programs to combat projected workforce shortages. However, such engagement is inherently complex as health centers are unique teaching settings with the primary function of healthcare delivery. The Readiness to Train Assessment Tool (RTAT) is a 41-item validated survey designed to measure organizational readiness for implementing HPT programs in health centers. Methods Between September 2020 and February 2021, the RTAT survey was distributed to all health center employees in the US and US territories. All participants were encouraged to complete the first subscale assessing the health center’s core readiness and commitment to HPT. Those with knowledge, involvement, or interest could select and evaluate specific HPT program(s) within four clinical discipline using the remaining six subscales. Scores were averaged over all participants from the same health center. Results Out of 1,466 targeted health centers nationwide, 1,063 health centers (72.5%) responded to the survey and assessed their readiness to engage, while 713 health centers continued the second portion of the survey to assess their readiness to implement at least one HPT program within four clinical disciplines for a total of 1,118 HPT programs assessed. Overall, within clinical disciplines, 10-14% of the health centers were still developing readiness, 48-59% were approaching readiness, and 27-42% were fully ready. Of note, there are a large portion of health centers approaching readiness and can reach full readiness by examining specific readiness areas at the survey item level to determine where barriers exist and where targeted strategies could improve their readiness. These results provide a national-level baseline for future comparisons and for making evidence-based decisions that drive regional and national policy choices for HPT at health centers. Conclusions In conclusion, the RTAT results were shared with health centers in an individualized, detailed report to fulfill a significant need to identify health centers’ core readiness and capacity to engage in health professions training and determine an appropriate course of action for individual health centers, primary care associations, policymakers, and health professions education and training leaders.